A modified EVA foam material and preparation method thereof

By adding PHBH to the EVA foaming material to form a phase separation structure and a three-dimensional network structure, the problems of large heat shrinkage and insufficient dimensional stability of EVA foaming material are solved, and better dimensional stability and thermal stability are achieved while maintaining the original performance.

CN119060449BActive Publication Date: 2025-04-18宁波致微新材料科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411560388.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-04-18
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

EVA foaming materials have large heat shrinkage and insufficient dimensional stability after foaming, which limits their application range in the shoe material manufacturing industry.

Method used

By adding PHBH to EVA, a phase separation structure and a three-dimensional network structure are formed, the elastic modulus of the cell wall is enhanced, the shrinkage rate is reduced, and the dimensional stability and thermal stability are improved.

Benefits of technology

It effectively improves the dimensional stability and heat shrinkage of EVA foamed materials, while maintaining the original rebound and permanent compression deformation ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the field of foaming materials, and specifically to a modified EVA foaming material and a preparation method thereof. A modified EVA foaming material comprises the following components in parts by weight: 75-90 parts of EVA, 10-25 parts of PHBH, and 0.1-1.0 parts of a cross-linking agent. The present application adds an appropriate amount of PHBH to EVA, forms an effective phase separation structure between PHBH and EVA, and then forms a three-dimensional network structure through a subsequent cross-linking structure, thereby effectively improving the dimensional stability and heat shrinkage rate of EVA after foaming; at the same time, due to the certain compatibility between PHBH and EVA, the original resilience and compression permanent deformation ability of EVA are maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of foaming materials, and in particular to a modified EVA foaming material and a preparation method thereof. Background Art

[0002] EVA (ethylene-vinyl acetate copolymer) is made by copolymerizing ethylene and vinyl acetate. Compared with polyethylene (PE), EVA introduces vinyl acetate monomer into the molecular chain, thereby increasing the branching degree of the polymer, improving flexibility, impact resistance, filler compatibility and heat sealing. The product has good softness, impact strength, environmental resistance, stress cracking, good optical properties, low temperature resistance and non-toxicity in a wide temperature range. Therefore, it is widely used in various fields.

[0003] EVA foam material refers to a foam material made by using EVA as raw material and adding foaming agent, cross-linking agent and other auxiliary agents through compression molding or injection molding. EVA foam material is a foam material with excellent foaming properties. It has many advantages such as light weight, low density, and load absorption. Therefore, it is widely used in various industries, especially in the foaming shoemaking industry, and is used in the soles and interior materials of mid-to-high-end tourist shoes, hiking shoes, slippers, and sandals.

[0004] However, after EVA is foamed alone, the heat shrinkage is large and the dimensional stability is insufficient. If materials such as PP (polypropylene) or PE (polyethylene) are added, although the dimensional stability and heat shrinkage can be improved to a certain extent, it will lead to insufficient resilience and excessive compression permanent deformation. Due to the above problems, the application scope of EVA foam materials in the shoe material manufacturing industry is limited. Therefore, how to improve the defects of EVA foam materials has become a technical problem that people in this technical field need to solve. Summary of the invention

[0005] In order to improve the problems of large heat shrinkage and insufficient dimensional stability of EVA foam materials without sacrificing the resilience and compression permanent deformation ability of EVA itself, the present application provides a modified EVA foam material, which effectively improves the dimensional stability and large heat shrinkage of EVA after foaming by adding PHBH to EVA, and maintains the original resilience and compression permanent deformation ability of EVA.

[0006] In the first aspect, the present application provides a modified EVA foam material, which adopts the following technical solution:

[0007] A modified EVA foaming material comprises the following components in parts by weight: 75-90 parts of EVA, 10-25 parts of PHBH and 0.1-1.0 parts of a cross-linking agent.

[0008] By adopting the above technical solution, EVA (ethylene-vinyl acetate copolymer) foaming materials often cause a certain amount of shrinkage after foaming due to the low glass transition temperature of EVA itself, the pressure difference between the inside and outside after foaming, and the gas exchange between the inside and outside of the pores. This lack of dimensional stability not only affects the appearance and size of the product, but may also affect its functionality and performance.

[0009] As a copolymer, PHBH (poly (3-hydroxybutyrate-co-3-hydroxyhexanoate)) has certain differences in molecular chain structure and physical properties from EVA. This difference enables PHBH to form an effective phase separation structure in the EVA matrix. This phase separation structure is mainly reflected in the dispersion of PHBH in the EVA matrix in the form of micro-nano particles, and then forming a three-dimensional network structure through subsequent cross-linking structure. This structure can provide additional support and stability for EVA during the foaming process, enhance the elastic modulus of the pore wall, thereby reducing the shrinkage of the overall material and improving dimensional stability.

[0010] In addition, the phase separation structure helps to disperse stress and further reduce the shrinkage of the material when heated. The cross-linking reaction strengthens the chemical bonds between the PHBH and EVA molecular chains, forming a multi-dimensional network structure, which further improves the thermal stability and dimensional stability of the material and reduces thermal shrinkage. At the same time, the addition of PHBH improves the pore structure of the foaming material, making the pores more stable and dense. This structure can not only resist dimensional changes caused by external factors and reduce thermal shrinkage, but also reduce the risk of pore rupture or collapse, ensuring that the material has a uniform pore structure.

[0011] Because PHBH and EVA have a certain degree of compatibility, but are not completely miscible to cause performance degradation. Adding an appropriate amount of PHBH can effectively improve the thermal shrinkage and dimensional stability of EVA while maintaining the original resilience and thermal deformation capacity of EVA.

[0012] The present application adds an appropriate amount of PHBH to EVA, forms an effective phase separation structure between PHBH and EVA, and then forms a three-dimensional network structure through subsequent cross-linking, thereby effectively improving the dimensional stability and thermal shrinkage rate of EVA after foaming; at the same time, due to the certain compatibility between PHBH and EVA, the original resilience and compression permanent deformation ability of EVA are maintained.

[0013] Preferably, the mass ratio of EVA to PHBH is 80:20.

[0014] By adopting the above technical solution, there is a certain degree of compatibility between EVA and PHBH, but they are not completely miscible. This moderate compatibility enables the two to form a stable phase structure during the mixing process, thereby exerting their respective advantages during the foaming process. When the PHBH content is too low, its improvement effect may be insufficient and cannot fully inhibit the shrinkage of EVA; when the PHBH content is too high, too much PHBH may destroy the molecular chain structure of EVA, resulting in a decrease in the material's resilience and compression permanent deformation ability.

[0015] The crosslinking agent is not particularly limited, and conventional peroxides such as BIPB and DCP may be cited. The amount added is usually 0.1-1.0 part, more preferably 0.2-0.5 part. Within this range, the polymer blend system has a suitable foaming window.

[0016] Preferably, the modified EVA foam material also includes an antioxidant.

[0017] By adopting the above technical solution, the addition of PHBH or its interaction with EVA may cause the material to be affected by external factors such as oxygen and light during processing, storage or use, resulting in oxidation reaction, causing yellowing on the surface or inside of the material, which affects the appearance of the material. Antioxidants are a type of additive that can significantly improve the oxidation resistance of materials. They can effectively capture and neutralize free radicals, thereby inhibiting or slowing down the oxidation reaction of materials in the presence of oxygen. By inhibiting the occurrence of oxidation reactions, antioxidants can significantly reduce the risk of yellowing of materials due to oxidation and maintain the appearance of the materials.

[0018] Preferably, the melting point of the antioxidant is in the range of 160-190°C.

[0019] By adopting the above technical solution, the foaming temperature is 150-180°C, the melting point of the antioxidant is 160-190°C, and the antioxidant begins to partially dissolve in the molten system of EVA and PHBH. This partially dissolved state makes the antioxidant particles gradually finer and more evenly dispersed in the substrate. Due to the refinement of the antioxidant particles, their surface area increases and the contact with the substrate becomes closer, thereby improving the dispersibility and stability of the antioxidant in the material.

[0020] The refined antioxidant particles can act as heterogeneous nucleation sites during the foaming process to promote the formation of microcrystals. During the foaming process, the gas expands in the substrate to form pores, and the presence of antioxidant particles provides additional nucleation sites for the formation of pores. These heterogeneous nucleation sites help to reduce the energy barrier for pore formation, resulting in an increase in the number of pores and a more uniform distribution. At the same time, due to the formation of microcrystals, the pore walls are strengthened, improving the stability and load-bearing capacity of the pore structure, thereby further improving the dimensional stability of the material.

[0021] This application not only utilizes the basic function of the antioxidant (preventing oxidation) by selecting an antioxidant with a melting point range near the temperature of the foaming process, but also further improves the material performance through its special behavior (partial dissolution, refinement and heterogeneous nucleation) during the foaming process.

[0022] Preferably, the modified EVA foam material also includes PHB.

[0023] By adopting the above technical solution, PHBH is a copolymer whose crystallization ability is generally poorer than that of a homopolymer, which is manifested by low crystal nucleus density and slow crystallization rate. PHB (poly-3-hydroxybutyrate) has a similar structure to PHBH, and the two have excellent compatibility. PHB is added to the polymer system to improve the crystallization ability of the polymer system, especially the crystallization behavior of PHBH. PHB can serve as an effective nucleation point in the blend melt, increase the density of crystal nuclei, and accelerate the crystallization process of PHBH.

[0024] The rapid and efficient crystallization process is conducive to the formation of more and finer PHBH crystallites, which helps to form a more stable and dense cell structure during the foaming process. When PHBH can crystallize quickly, its molecular chains are effectively fixed in the crystal structure, reducing the molecular chain slippage and deformation caused by thermal expansion or mechanical stress. This stable cell structure can resist dimensional changes caused by external factors, thereby improving the dimensional stability of the modified EVA foam material.

[0025] Compared with traditional inorganic nucleating agents, PHB has better dispersibility and compatibility as a nucleating agent. Inorganic nucleating agents are often difficult to disperse evenly in polymer melts and may interact adversely with polymer substrates. PHB has a similar structure to PHBH and can be better compatible with PHBH and evenly distributed in it. Therefore, PHB is more effective as a nucleating agent than traditional inorganic nucleating agents, and can more effectively improve the crystallization properties of PHBH and improve the overall performance of modified EVA foaming materials.

[0026] Preferably, the modified EVA foam material further comprises PHB and an antioxidant.

[0027] By adopting the above technical solution, when antioxidants are used alone, although they can effectively inhibit oxidation reactions, due to their limited solubility in the EVA-PHBH eutectic system, they are easily precipitated, resulting in the antioxidant effect gradually weakening over time. As a natural polymer material, PHB itself has certain antioxidant properties, can form good compatibility with the EVA-PHBH system, and can play a certain antioxidant effect. Therefore, when PHB is used in combination with antioxidants, the two can work synergistically to form a more stable antioxidant barrier, significantly improving the overall antioxidant performance of the material.

[0028] The combined use of PHB and antioxidants can effectively slow down the oxidation process of materials, thereby reducing the performance degradation of materials caused by oxidation during use, such as yellowing of color.

[0029] The addition of PHB can not only improve the antioxidant properties of the material, but also have a positive effect on the microstructure of the material. For example, a more complex phase separation structure or interpenetrating network structure may be formed between PHB and EVA-PHBH, which helps to enhance the overall strength and toughness of the material. At the same time, this structure also helps to better fix the antioxidant molecules and reduce their precipitation, thereby improving the durability of the antioxidant effect.

[0030] In a second aspect, the present application provides a method for preparing a modified EVA foam material, using the following technical solution:

[0031] A method for preparing a modified EVA foam material comprises the following steps:

[0032] Primary mixing: Mix the formulated amount of EVA and PHBH to obtain the primary mixing product;

[0033] Re-mixing: adding a formulated amount of a cross-linking agent to the primary mixed product for mixing to obtain a re-mixed product;

[0034] Tableting: tabletting the re-mixed product to obtain a sheet;

[0035] Heating and gas injection: the sheet is heated and stirred, and high-pressure gas is introduced, wherein the pressure of the high-pressure mixed gas is 12-15 MPa;

[0036] Pressure relief transformation: After the high-pressure gas in the sheet material reaches saturation, the pressure is released and the sheet material is transformed into a modified EVA foam material.

[0037] By adopting the above technical solution, EVA and PHBH can be fully mixed during the initial mixing, so that the molecular chains of the two are better entangled with each other, improving the uniformity and consistency of the base material. During the secondary mixing, a cross-linking agent is added, which can form chemical bonds between the molecular chains of EVA and PHBH, increase the cross-linking density of the molecular chains, and thus improve the strength, heat resistance and solvent resistance of the material.

[0038] After the high-pressure gas is saturated, the system is supersaturated by decompression, and the supercritical fluid forms a large number of gas cores inside the material. As the gas continues to diffuse into the gas cores, these gas cores gradually grow and connect with each other, eventually forming a pore structure. High-pressure conditions help to ensure the uniform distribution of gas cores and the stability of the pore structure. At the same time, the use of high-pressure gas can also adjust the density and performance of the foaming material as needed. During the decompression process, the gas continues to expand and pushes the molecular chains inside the material to form a stable pore structure. Rapid and uniform decompression helps reduce the risk of pore rupture and collapse, thereby obtaining high-quality foaming materials.

[0039] Preferably, in the step of heating and gas injection, the temperature range of the heating and stirring is 150-180°C.

[0040] By adopting the above technical solutions, polymer materials such as EVA (ethylene-vinyl acetate copolymer) and PHBH (poly (3-hydroxybutyrate-co-3-hydroxyhexanoate)) are prone to thermal degradation or thermal oxidation at high temperatures, resulting in a decrease in material performance, such as reduced strength and yellowing. If the heating temperature exceeds the heat resistance limit of the material, these adverse reactions will be accelerated, thereby affecting the quality of the final product.

[0041] The appropriate heating temperature helps the gas to enter the foaming material better, thus forming an ideal cell structure. If the heating temperature is too low, the melt strength of the polymer system is too high, and the foaming effect may not be ideal, such as low foaming ratio, insufficient cell density, uneven cell size, etc.

[0042] Preferably, in the step of heating and injecting gas, the high-pressure gas is a mixed gas of CO2 and N2, and the volume ratio of CO2 to N2 is 1:1-3.

[0043] By adopting the above technical solution, CO2 and N2 can play a synergistic role in the foaming process. CO2 has a high solubility and diffusion rate, and can quickly enter the polymer matrix to form bubble nuclei and promote the expansion of the pores. N2 helps nucleation, maintains the stability of the pore structure, and prevents the pores from rupturing or collapsing.

[0044] When the volume ratio of CO2 and N2 is set within the range of 1:1 to 1:3, a better foaming effect can be obtained. This ratio range allows CO2 and N2 to give full play to their respective advantages and achieve a better synergistic state. At the same time, it can also avoid the shortcomings and defects of using a single gas.

[0045] Preferably, in the initial mixing step, the formulated amount of PHB and / or antioxidant is mixed with EVA and PHBH to obtain an initial mixing product.

[0046] By adopting the above technical solution, the antioxidant can effectively capture and neutralize free radicals, thereby delaying the oxidative degradation process of the material and improving the antioxidant performance of the material. The addition of PHB can enhance the intermolecular interaction force of the EVA and PHBH blend system and promote the uniformity and density of the material. EVA, PHBH and PHB have certain similarities in chemical structure, which makes them easier to disperse evenly during the mixing process. Adding PHB during the initial mixing helps to promote the compatibility between the three materials. The hydroxyl group of PHB itself can have a certain antioxidant ability by capturing some free radicals. When it works synergistically with antioxidants, it can more effectively inhibit the oxidative degradation process of the material and extend the service life of the material. Some antioxidants with a melting point near the foaming temperature can act as nucleating agents, promote the formation of bubble nuclei, and help to obtain a more uniform and finer pore structure, thereby improving the dimensional stability of the material and improving the problem of large thermal shrinkage.

[0047] As a bio-based material, PHB has good compatibility with the EVA-PHBH system and can be used as an effective heterogeneous nucleating agent to promote the formation and stability of bubble nuclei during the foaming process. Its effect is often better than that of traditional inorganic nucleating agents because bio-based materials usually have better interfacial compatibility and environmental friendliness. PHB itself also has certain antioxidant properties, which can further enhance the antioxidant effect of the material and form a synergistic effect with antioxidants.

[0048] According to specific needs and product performance indicators, you can choose to add antioxidants, PHB, or both. This flexibility makes the formula design more precise and can meet the performance requirements of different application scenarios.

[0049] In summary, this application has the following beneficial effects:

[0050] 1. The present invention adds an appropriate amount of PHBH to EVA, forms an effective phase separation structure between PHBH and EVA, and then forms a three-dimensional network structure through subsequent cross-linking, thereby effectively improving the dimensional stability and thermal shrinkage rate of EVA after foaming; at the same time, due to the certain compatibility between PHBH and EVA, the original resilience and compression permanent deformation capacity of EVA are maintained;

[0051] 2. This application not only utilizes the basic function of the antioxidant (preventing oxidation) by selecting an antioxidant with a melting point range near the temperature of the foaming process, but also further improves the material performance through its special behavior (partial dissolution, refinement and heterogeneous nucleation) during the foaming process;

[0052] 3. In the present application, PHB is added as a heterogeneous nucleating agent, which can serve as an effective nucleation point in the PHBH melt, increase the density of crystal nuclei, and accelerate the crystallization process of PHBH; PHB itself also has a certain antioxidant property, which can enhance the antioxidant effect of the material. DETAILED DESCRIPTION

[0053] The raw materials in this application include the following parts:

[0054] EVA: ethylene-vinyl acetate copolymer, a commercial product with CAS number 24937-78-8;

[0055] PHBH: poly (3-hydroxybutyrate-co-3-hydroxyhexanoate), a commercial product with CAS number 147398-31-0;

[0056] Cross-linking agent: cross-linking agents such as BIPB and DCP can be used. This application only uses commercially available products of BIPB as an example;

[0057] PE: Use a commercial product with CAS No. 9002-88-4;

[0058] PHBV: a commercial product with CAS number 80181-31-3 was used;

[0059] PHB: commercially available product using poly-3-hydroxybutyrate;

[0060] Antioxidant: commercially available products of antioxidant 1024, antioxidant LK-1081, antioxidant 626, antioxidant CA and antioxidant 330 are used;

[0061] CO2: Use a commercial product with CAS number 124-38-9;

[0062] N2: Use a commercially available product with CAS number 7727-37-9;

[0063] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0064] Example 1

[0065] A method for preparing a modified EVA foam material comprises the following steps:

[0066] Initial mixing: first add 80g of EVA and 20g of PHBH into a mixer and mix for 10min at a mixing temperature of 180℃ to obtain an initial mixing product;

[0067] Re-mixing: cool the initial mixed product to 110°C, add 0.3g of cross-linking agent BIPB to the initial mixed product, the cross-linking agent BIPB can be 0.1-1.0g, and this application only uses 0.3g BIPB as an example, mix for 5 minutes, and obtain a re-mixed product;

[0068] Tableting: Tablet the re-mixed product at 180°C for 10 min to obtain a sheet;

[0069] Heating and gas injection: the sheet is placed in a high temperature and high pressure container at a temperature of 170°C, and a high pressure gas is introduced. The gas is CO2, and the pressure of the high pressure gas is 14MPa. The pressure of the high pressure gas can be 12-15MPa. This application only takes 14MPa as an example;

[0070] Pressure relief transformation: After 6 hours, the gas in the sheet reaches saturation, the pressure is released, and the sheet is transformed into a modified EVA foam material.

[0071] Example 2-3

[0072] Example 2-3 Based on the preparation method of Example 1, the content of each component of the modified EVA foam material is adjusted, and the specific adjustment is shown in Table 1.

[0073] Comparative Examples 1-5

[0074] Comparative Example 1 Based on the preparation method of Example 1, 70 g of EVA and 30 g of PHBH were added, and the other conditions remained unchanged.

[0075] Comparative Example 2: Based on the preparation method of Example 1, 100 g of EVA was added, and the other conditions remained unchanged.

[0076] Comparative Example 3: Based on the preparation method of Example 1, 80 g of EVA and 20 g of PE were added, and the other conditions remained unchanged.

[0077] Comparative Example 4: Based on the preparation method of Example 1, 80 g of EVA and 20 g of PHBV were added, and the other conditions remained unchanged.

[0078] Comparative Example 5: Based on the preparation method of Example 1, 80 g of EVA and 20 g of PHB were added, and the other conditions remained unchanged.

[0079] Table 1 Contents of components and performance test of modified EVA foam materials of Examples 1-3 and Comparative Examples 1-5

[0080]

[0081] Performance testing

[0082] The modified EVA foam materials of Examples 1-3 and Comparative Examples 1-5 were subjected to the following performance tests, and the test results are shown in Table 1.

[0083] 1. Dimensional stability

[0084] Using the drainage method (ASTM D792), the density of the sheet and modified EVA foam material are marked as ρ s and ρ f , the foaming ratio is calculated by the formula B=ρ s / ρ f The expansion ratio when the sample is just taken out is defined as B1, the expansion ratio measured after 24 hours is defined as B2, and the final shrinkage after 24 hours is S=[(B1-B2) / B1]*100%.

[0085] 2. Thermal shrinkage

[0086] Referring to the determination method of GB / T 8811-2008, the modified EVA foam material was made into a sample with a size of (100±1) mm*(100±1) mm*(25±0.5) mm. The test was carried out after conditioning for 72 hours at a temperature of (23±2)°C and a relative humidity of 45%~55%. The length L0 and width W0 of each sample at different positions were measured first, and then the sample was placed in a constant temperature oven at (70±2)°C for 1 hour, and then the length L of the sample was measured after it was taken out and placed at a temperature of (23±2)°C and a relative humidity of 45%~55% for 1 hour. t and width W t The thermal shrinkage rate of the sample length L = [(L0-L t ) / L0]*100%, the thermal shrinkage rate of the sample width W = [(W0-W t ) / W0]*100%. The above two thermal shrinkage values ​​are averaged to obtain the thermal shrinkage value.

[0087] 3. Resilience

[0088] Referring to the determination method of GB / T 6670-2008 Method A, the modified EVA foam material is made into a sample with a size of (100±1) mm*(100±1) mm*(50±0.5) mm. The test is carried out after conditioning for 72 hours at a temperature of (23±2)℃ and a relative humidity of (50±5)%. A transparent tube with an inner diameter of 50 mm is selected, and a scale line is drawn on the outside of the tube. A steel ball with a diameter of 16 mm±0.5 mm and a mass of 16.8 g±1.5 g is selected. The sample is placed on the reference surface, and the tube is fixed to ensure that there is a light contact between the tube and the sample without causing any visible pressure. The steel ball is placed on the release device to release the steel ball, and the maximum rebound height value is recorded. It should not touch the inner wall of the tube. Multiple measurements are taken, and the median value is taken as the rebound rate of the sample.

[0089] 4. Compression set

[0090] With reference to the determination method of GB / T 6669-2008, the modified EVA foam material was made into a specimen with a length and width of (50±1) mm and a thickness of (25±1) mm. After conditioning for 72 hours at a temperature of (23±2)°C and a relative humidity of (50±5)%, its initial thickness d0 was measured. The specimen was placed between the two plates of the device and compressed by 50%±4% of its thickness. Within 15 minutes, the compressed specimen was placed in an oven at (50±1)°C and maintained in this state for (6±0.2) hours. The device was removed from the oven and the specimen was removed within 1 minute. The specimen was placed on the surface of a low thermal conductivity object to cool for (30±5) minutes. The final thickness d0 of the specimen was measured. t , calculate the compression set CS = [(d0-d t ) / d0]*100%.

[0091] 5. Color

[0092] Observe the surface color of each sample and record it.

[0093] Referring to Table 1, by comparing Examples 1-3 and Comparative Examples 1-5, it can be seen that, compared with Comparative Example 2, the final shrinkage and thermal shrinkage of Examples 1-3 are much lower than those of Comparative Example 2, the rebound rates are higher than those of Comparative Example 2, and the compression permanent deformation is lower than that of Comparative Example 2 or slightly higher than that of Comparative Example 2, indicating that the addition of PHBH to EVA can improve the dimensional stability of the foaming material, and does not affect the higher resilience and lower compression permanent deformation of EVA itself.

[0094] Compared with Comparative Examples 2-3, the final shrinkage and thermal shrinkage of Comparative Example 3 are lower than those of Comparative Example 2, but the rebound rate of Comparative Example 3 is much lower than that of Comparative Example 2, and the compression permanent deformation of Comparative Example 3 is much higher than that of Comparative Example 2, indicating that when PE is added to EVA, although it can improve the dimensional stability of the foaming material, it will still affect the higher resilience and lower compression permanent deformation capacity of EVA itself.

[0095] Compared with Comparative Examples 4-5, the final shrinkage and thermal shrinkage of Example 1 are slightly lower than those of Comparative Examples 4-5, the rebound rate of Example 1 is higher than that of Comparative Examples 4-5, and the compression permanent deformation of Example 1 is lower than that of Comparative Example 5. The final shrinkage and thermal shrinkage of Comparative Examples 4-5 are lower than those of Comparative Example 2, but the rebound rate of Comparative Example 4 is much lower than that of Comparative Example 2, and the compression permanent deformation of Comparative Examples 4-5 is much higher than that of Comparative Example 2, indicating that when PHBV or PHB is added to EVA, although the dimensional stability of the foaming material can be improved, it will still affect the high resilience and low compression permanent deformation capacity of EVA itself.

[0096] By color comparison, it is found that the colors of the foaming materials of Example 1, Example 3 and Comparative Example 1 are all yellow, the color of Example 2 is slightly yellow, and the color of Comparative Example 2 is white, indicating that as the content of PHBH increases, oxidation reaction is more likely to occur during the preparation process, resulting in yellowing.

[0097] In addition, by comparing Examples 1-3, it is found that, except for the color, the performance of Example 1 is the best, and therefore, Example 1 is preferred.

[0098] Embodiment 4-8

[0099] Example 4 Based on the preparation method of Example 1, 0.6 g of antioxidant 1024 is mixed with 80 g of EVA and 20 g of PHBH to obtain a primary mixed product. The melting point of antioxidant 1024 is 60-67°C, and the other conditions remain unchanged.

[0100] Example 5 Based on the preparation method of Example 1, 0.6 g of antioxidant LK-1081 is mixed with 80 g of EVA and 20 g of PHBH to obtain a primary mixed product. The melting point of antioxidant LK-1081 is 166-168°C, and other conditions remain unchanged.

[0101] Example 6 Based on the preparation method of Example 1, 0.6 g of antioxidant 626 is mixed with 80 g of EVA and 20 g of PHBH to obtain a primary mixed product. The melting point of antioxidant 626 is 160-180°C, and other conditions remain unchanged.

[0102] Example 7 Based on the preparation method of Example 1, 0.6 g of antioxidant CA is mixed with 80 g of EVA and 20 g of PHBH to obtain a primary mixed product. The melting point of antioxidant CA is 183-190°C, and other conditions remain unchanged.

[0103] Example 8 Based on the preparation method of Example 1, 0.6 g of antioxidant 330 is mixed with 80 g of EVA and 20 g of PHBH to obtain a primary mixed product. The melting point of antioxidant 330 is 242-246°C, and other conditions remain unchanged.

[0104] The modified EVA foam materials of Examples 4-8 were subjected to the above performance tests, and the test results are shown in Table 2.

[0105] Table 2 Antioxidant melting point range and performance test table of Example 1 and Examples 4-8

[0106]

[0107] Referring to Table 2, by comparing Example 1 with Examples 4-8, it can be seen that the addition of an antioxidant can effectively improve the yellowing phenomenon, thereby effectively improving the color of the foaming material.

[0108] The heating temperature during foaming is 175°C. As the melting point of the antioxidant increases, the final shrinkage and thermal shrinkage both show a trend of first decreasing and then increasing. This may be because as the melting point of the antioxidant increases and gets closer to the heating temperature of 175°C, the antioxidant is converted from complete dissolution at a low melting point to partial dissolution. This partially dissolved state makes the antioxidant particles gradually refined. The refined antioxidant particles can serve as heterogeneous nucleation points during the foaming process, promote the formation of microcrystals, strengthen the pore wall, improve the stability and load-bearing capacity of the pore structure, and further improve the dimensional stability of the material and improve the thermal shrinkage.

[0109] However, when the melting point of the antioxidant exceeds the heating temperature during foaming, the antioxidant is difficult to melt, and the antioxidant particles are relatively large. The effect of the antioxidant particles as heterogeneous nucleation points is not as good as that of the refined antioxidant particles, which reduces the degree of improvement in the dimensional stability of the foamed material.

[0110] Examples 9-12

[0111] Example 9 Based on the preparation method of Example 1, 1 g of PHB, 80 g of EVA and 20 g of PHBH are mixed together to obtain a primary mixed product, and the other conditions remain unchanged.

[0112] Example 10 Based on the preparation method of Example 1, 2 g of PHB, 80 g of EVA and 20 g of PHBH are mixed together to obtain a primary mixed product, and the other conditions remain unchanged.

[0113] Example 11 Based on the preparation method of Example 1, 2 g of talcum powder, 80 g of EVA and 20 g of PHBH are mixed together to obtain a primary mixed product, and the other conditions remain unchanged.

[0114] Example 12 Based on the preparation method of Example 1, 2 g of calcium carbonate, 80 g of EVA and 20 g of PHBH are mixed together to obtain a primary mixed product, and the other conditions remain unchanged.

[0115] The modified EVA foam materials of Examples 9-12 were subjected to the above performance tests, and the test results are shown in Table 3 respectively.

[0116] Table 3 Performance test table of Example 1 and Examples 9-12

[0117]

[0118] Referring to Table 3, by comparing Example 1 with Examples 9-12, it can be seen that the addition of PHB or an inorganic nucleating agent can further improve the dimensional stability of the foaming material. In comparison, the addition of PHB has a better effect on improving the dimensional stability of the foaming material than the inorganic nucleating agent. This may be because PHB (poly-3-hydroxybutyrate), as a polymer with a similar structure to PHBH but better crystallization performance, is used as a heterogeneous nucleating agent and added to the modified EVA foaming material. PHB can serve as an effective nucleation point in the PHBH melt, increase the density of the crystal nucleus, and accelerate the crystallization process of PHBH.

[0119] The fast and efficient crystallization process helps to form a more stable and dense cell structure during the foaming process. When PHBH can crystallize quickly, its molecular chains are effectively fixed in the crystal structure, reducing the molecular chain slip and deformation caused by thermal expansion or mechanical stress. This stable cell structure can resist dimensional changes caused by external factors, thereby improving the dimensional stability of the modified EVA foam material. Compared with traditional inorganic nucleating agents, PHB has better dispersibility and compatibility as a heterogeneous nucleating agent. Inorganic nucleating agents are often difficult to disperse evenly in polymer melts.

[0120] Examples 13-16

[0121] Example 13 Based on the preparation method of Example 6, 1 g of PHB is mixed with 80 g of EVA, 20 g of PHBH and 0.6 g of antioxidant 626 to obtain a primary mixed product, while other conditions remain unchanged.

[0122] Example 14 Based on the preparation method of Example 6, 2 g of PHB is mixed with 80 g of EVA, 20 g of PHBH and 0.6 g of antioxidant 626 to obtain a primary mixed product, while other conditions remain unchanged.

[0123] Example 15 Based on the preparation method of Example 6, 2 g of talcum powder is mixed with 80 g of EVA, 20 g of PHBH and 0.6 g of antioxidant 626 to obtain a primary mixed product, and the other conditions remain unchanged.

[0124] Example 16 Based on the preparation method of Example 6, 2 g of calcium carbonate is mixed with 80 g of EVA, 20 g of PHBH and 0.6 g of antioxidant 626 to obtain a primary mixed product, while other conditions remain unchanged.

[0125] The modified EVA foam materials of Examples 13-16 were subjected to the above performance tests, and the test results are shown in Table 4 respectively.

[0126] Table 4 Performance test table of Example 6 and Examples 13-16

[0127]

[0128] Referring to Table 4, by comparing Example 6 with Examples 13-16, it can be seen that the final shrinkage of Examples 17-18 is lower than that of Example 6. The material color of Examples 17-18 is white, while the material color of Example 6 is white, indicating that PHB and antioxidant 626 can produce a synergistic effect, which can not only improve the antioxidant effect in the preparation process, but also further improve the dimensional stability of the foamed material.

[0129] Examples 17-18

[0130] In Examples 17-18, based on the preparation method of Example 1, the heating temperature in the heating and gas injection step is adjusted. The specific adjustments are shown in Table 5.

[0131] Comparative Examples 6-7

[0132] In Comparative Example 6-7, based on the preparation method of Example 1, the heating temperature in the heating and gas injection step was adjusted. The specific adjustments are shown in Table 5.

[0133] The modified EVA foam materials of Examples 17-18 and Comparative Examples 6-7 were subjected to the above performance tests, and the test results are shown in Table 5.

[0134] Table 5 Heating temperature and performance test table of Example 1, Examples 17-18 and Comparative Examples 6-7

[0135]

[0136] Referring to Table 5, it can be seen from the comparison of Example 1, Examples 17-18 and Comparative Examples 6-7 that as the heating temperature continues to increase, the final shrinkage and thermal shrinkage both show a trend of first decreasing and then increasing. This may be because as the heating temperature continues to increase, it helps the mixed gas to better enter the foaming material and form an ideal cell structure. When the temperature exceeds a certain range, EVA and PHBH are prone to thermal degradation or thermal oxidation at high temperatures, resulting in a decrease in material performance. If the heating temperature exceeds the heat resistance limit of the material, these adverse reactions will be accelerated, thereby reducing the dimensional stability of the foaming material and exacerbating the problem of large thermal shrinkage.

[0137] Examples 19-22

[0138] Example 19 is based on the preparation method of Example 1, with the high-pressure gas replaced by a mixed gas, in which the volume ratio of CO2 and N2 in the mixed gas is 1:2, and other conditions remain unchanged.

[0139] In Examples 20-22, based on the preparation method of Example 1, the volume ratio of CO2 and N2 is adjusted. The specific adjustments are shown in Table 6.

[0140] The modified EVA foam materials of Examples 19-22 were subjected to the above performance tests, and the test results are shown in Table 6 respectively.

[0141] Table 6 Volume ratio performance test table of CO2 and N2 of Example 1 and Examples 19-22

[0142]

[0143] Referring to Table 6, by comparing Example 1 with Examples 19-22, it can be seen that the mixed gas composed of CO2 and N2 is more conducive to the foaming of the foaming material than adding the two gases separately.

[0144] As the volume ratio of CO2 and N2 increases, the final shrinkage and thermal shrinkage both show a trend of first decreasing and then increasing. This may be because as the volume ratio of CO2 and N2 increases, the content of CO2 increases. CO2 has a higher solubility and diffusion rate, and can quickly enter the polymer matrix to form bubble nuclei and promote the expansion of the pores, thereby obtaining a better foaming effect. The remaining N2, due to its inertness and low migration rate, helps to maintain the stability of the pore structure and prevent the pores from rupturing or collapsing, thereby maintaining better dimensional stability.

[0145] When the volume ratio of CO2 and N2 exceeds a certain range, the CO2 content is too high and the N2 content is relatively low, the foam cells expand excessively, and there is insufficient N2 to maintain the stability of the foam structure, which reduces the dimensional stability of the foaming material and increases the thermal shrinkage rate.

[0146] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A modified EVA foam material, characterized in that: The invention comprises the following components in parts by weight: 75-90 parts of EVA, 10-25 parts of PHBH, and 0.1-1.0 parts of a cross-linking agent; Also includes an antioxidant, the melting point range of the antioxidant is 160-190°C; The preparation method of the modified EVA foam material comprises the following steps: Primary mixing: Mix the formulated amount of EVA, PHBH and antioxidant to obtain the primary mixing product; Re-mixing: adding a formulated amount of a cross-linking agent to the primary mixed product for mixing to obtain a re-mixed product; Tableting: tabletting the re-mixed product to obtain a sheet; Heating and gas injection: heating and stirring the sheet, introducing high-pressure gas, the heating temperature range is 150-180°C, and the pressure of the high-pressure gas is 12-15MPa; Pressure relief transformation: After the high-pressure gas in the sheet reaches saturation, the pressure is released and the sheet is transformed into a modified EVA foaming material.

2. The modified EVA foam material according to claim 1, characterized in that: It also includes PHB. In the initial mixing step, the formulated amount of PHB and antioxidant are mixed with EVA and PHBH to obtain the initial mixing product.

3. The modified EVA foam material according to claim 1, characterized in that: In the step of heating and injecting gas, the high-pressure gas is a mixed gas of CO2 and N2, and the volume ratio of CO2 to N2 is 1:1-3.

Citation Information

Patent Citations

  • A bio-based thermoplastic elastomer material and a preparation method thereof

    CN103642183A